The use of hands on activities in the development of english reading skills through pedagogical interactive guidance in fourth grade at unidad educativa Bautista Israel primary school - Saavedra Ordoñez, Heidy Arleth (2017)
Reading is an essential part of language instruction at every level, the mind, imagination and creativity will be developing through this skill. This research is about an institution which not exceeded of two hundred students and teachers until two years ago. The new staffs of teachers have the opportunity to work with elemental English with simple instructions in which students learn English little by little. In this case students manipulate their own work in order to construct their own knowledge. People have complication with reading. Many people say that reading is difficult to understand, and also, comprehend a lecture is a waste of time. Although, is important to know that Reading is an important skill and necessary in job‘s interviews. It has some benefits, such as helps to expand the mind and creativity. Read a book or articles are really important because it help to increase our knowledge and give opinions about any topics……